2017
DOI: 10.1080/09712119.2017.1411266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and sex on carcass characteristics and internal organ weights of scavenging chickens and helmeted guinea fowls

Abstract: The objective of the study was to determine the effect of age and sex on carcass characteristics and internal organ weights in scavenging guinea fowls and chickens. Ninety-six scavenging birds, purchased from farmers, were used comprising 48 guinea fowls and 48 chickens from communal farmers. Guinea fowls comprised 25 females and 23 males, with 21 growers and 27 adults. Chickens had 18 females and 30 males with 19 growers and 29 adults. Guinea fowls had heavier body weight and relative hot carcass and cold dre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
3
7
5
2
Order By: Relevance
“…Similar conclusions were also obtained by Tasoniero et al [ 31 ], who demonstrated the important role of sex in heart weight formation in two Italian local breeds. Interestingly, these observations do not correspond to those reported by Musundire et al [ 32 ], who did not demonstrate a significant influence of bird sex on heart size.…”
Section: Discussioncontrasting
confidence: 96%
“…Similar conclusions were also obtained by Tasoniero et al [ 31 ], who demonstrated the important role of sex in heart weight formation in two Italian local breeds. Interestingly, these observations do not correspond to those reported by Musundire et al [ 32 ], who did not demonstrate a significant influence of bird sex on heart size.…”
Section: Discussioncontrasting
confidence: 96%
“…Univariate analyses revealed significant differences among zones for most zoometric traits and calculated body indices, suggesting the possible influence of these zones on the evolutionary adaptation of the sheep population in terms of these. They are however, higher than the range 1.08-1.33 kg reported for adult guinea fowl (Numida meleagris) in a humid zone of southern Nigeria [60] and 1.275 kg obtained in Zimbabwe [61]. However, the indigenous birds are smaller in size when compared to their exotic counterparts.…”
Section: Discussionmentioning
confidence: 55%
“…They are however, higher than the range 1.08-1.33 kg reported for adult guinea fowl (Numida meleagris) in a humid zone of southern Nigeria [60] and 1.275 kg obtained in Zimbabwe [61]. However, the indigenous birds are smaller in size when compared to their exotic counterparts.…”
Section: Decision Trees Of the Data Miningmentioning
confidence: 55%
“…La crianza de N. meleagris tiene ventajas considerables; por ejemplo, las aves se adaptan a diversas condiciones agroclimáticas, consumen una gran variedad de alimentos no convencionales, tienen la capacidad de protegerse ante depredadores, controlan las garrapatas y otras plagas, son tolerantes a la mayoría de las enfermedades comunes de las aves de corral y no se requiere demasiada mano de obra e infraestructura costosa para su manejo (Ebegbulem, 2018;Koné et al, 2018;Musundire et al, 2018). Productivamente, la gallina de Guinea también presenta buena ganancia de peso, conversión alimenticia (Houndonougbo et al, 2017;EleroÄŸlu et al, 2018) y rendimiento de la canal (Mareko et al, 2006;Chiroque et al, 2018), aun cuando es comparado con el rendimiento de la canal del pollo (Musundire et al, 2018).…”
Section: Introductionunclassified
“…La crianza de N. meleagris tiene ventajas considerables; por ejemplo, las aves se adaptan a diversas condiciones agroclimáticas, consumen una gran variedad de alimentos no convencionales, tienen la capacidad de protegerse ante depredadores, controlan las garrapatas y otras plagas, son tolerantes a la mayoría de las enfermedades comunes de las aves de corral y no se requiere demasiada mano de obra e infraestructura costosa para su manejo (Ebegbulem, 2018;Koné et al, 2018;Musundire et al, 2018). Productivamente, la gallina de Guinea también presenta buena ganancia de peso, conversión alimenticia (Houndonougbo et al, 2017;EleroÄŸlu et al, 2018) y rendimiento de la canal (Mareko et al, 2006;Chiroque et al, 2018), aun cuando es comparado con el rendimiento de la canal del pollo (Musundire et al, 2018). Otra cualidad relevante de esta ave es la calidad nutricional de su carne, ya que se ha determinado el alto contenido de minerales y ácidos grasos esenciales (Bernacki et al, 2012), además de su alto contenido proteico y bajo contenido de grasa (Hoffman y Tihong, 2012), características que mejoran cuando las aves son criadas de manera semi-intensiva o "al aire libre" (Sarica et al, 2019).…”
Section: Introductionunclassified